2017
DOI: 10.5301/ejo.5000937
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Eyelid Laxity and its Association with Ophthalmic Findings and Disease Severity in Patients with Keratoconus

Abstract: Higher prevalence and greater eyelid laxity were found in patients with KC compared to healthy participants. However, eyelid laxity was not associated with severity of KC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Keratoconus has been associated with atopia, 11, 12 vernal keratoconjunctivitis, 13-15 and environmental factors such as persistent eye rubbing and eyelid laxity. 16, 17 There is a higher prevalence of keratoconus in patients with Downs syndrome; 18 however, the genetic correlation has not been conclusive and the presence of keratoconus in these patients is likely associated to persistent eye rubbing. Other genetic conditions such as Leber’s congenital amaurosis 19 and mitral valve prolapse 1, 20, 21 have been genetically linked to Keratoconus, and numerous publications show a strong genetic predisposition, 22-24 with identified potential linked genes.…”
Section: Keratoconus: Epidemiologymentioning
confidence: 99%
“…Keratoconus has been associated with atopia, 11, 12 vernal keratoconjunctivitis, 13-15 and environmental factors such as persistent eye rubbing and eyelid laxity. 16, 17 There is a higher prevalence of keratoconus in patients with Downs syndrome; 18 however, the genetic correlation has not been conclusive and the presence of keratoconus in these patients is likely associated to persistent eye rubbing. Other genetic conditions such as Leber’s congenital amaurosis 19 and mitral valve prolapse 1, 20, 21 have been genetically linked to Keratoconus, and numerous publications show a strong genetic predisposition, 22-24 with identified potential linked genes.…”
Section: Keratoconus: Epidemiologymentioning
confidence: 99%
“…В связи с этим пациенты предъявляют разнооб разные жалобы, такие как постоянное покраснение глаза, ощущение инородного тела в глазу, дискомфорт, слизистое отделяемое, не поддающиеся консервативному лечению. Помимо вышеперечисленных признаков, имеются данные о других офтальмологических проявлениях, к которым относится патология роговицы: кератоконус [9][10][11][12], аномалии положения векзаворот/выворот ниж них век, частичный блефароптоз [7,13,14], птоз ресниц, глаукома [15]. СГВ также часто ассоциируется с системными заболеваниями, среди них чаще всего встречаются ожирение, гипертоническая болезнь, ишемическая болезнь сердца, сахарный диабет и синдром обструктивного апноэ сна (СОАС) [16][17][18][19].…”
Section: обоснованиеunclassified
“…Floppy eyelid syndrome (FES) is characterised by a thin, rubbery upper tarsus that can be folded upon itself and easily everted with upward traction due to abnormal eyelid and tarsal laxity, accompanied by diffuse reactive palpebral papillary conjunctivitis with or without the presence of symptoms of ocular surface inflammation [158]. It can lead to significant ocular irritation and its coexistence with keratoconus has been well reported in the literature [159][160][161]. Many studies have found a significantly higher level of FES in KC patients (up to 71%) [161,162].…”
Section: (D) Release Of Inflammatory Mediatorsmentioning
confidence: 99%
“…It can lead to significant ocular irritation and its coexistence with keratoconus has been well reported in the literature [159][160][161]. Many studies have found a significantly higher level of FES in KC patients (up to 71%) [161,162]. The mechanism, though, behind its contribution to the pathogenesis/progression of keratoconus remains unknown.…”
Section: (D) Release Of Inflammatory Mediatorsmentioning
confidence: 99%
See 1 more Smart Citation